A modified technique for scrotal fixation during orchiopexy - Wagih M Ghnnam; Basem Saed; Hosam Ghazy (Wolters Kluwer Medknow Publications, 2011)
Background: Undescended testes are a common problem, affecting up to 3% of newborn males. The goals of orchiopexy in humans are to provide adequate scrotal fixation, to prevent recurrent torsion of the testis and spermatic cord or ascent of the testis, and to achieve these goals with minimal trauma to the testis. The best method of achieving fixation remains controversial. Purpose: The aim of our study is to evaluate our modified extra Dartos pouch technique in retaining testis in the scrotum. Patients and Methods: A prospective randomized study included 159 patients with 185 orchiopexies age ranging from 5 months to 14 years with the mean age of 49.5 ΁ 33.3 months (4.08 years). They were divided into two groups: Group I for whom the extra Dartos pouch technique was applied were compared to Group II for whom classic sub-Dartos pouch technique was done. Results: Testis was located in the superficial inguinal pouch in 102 cases (64.1%) and intra-canalicular in 57 cases (35.6%). Hernial sac was found in 153 cases (96.2%), postoperative wound infection occurred in 3 cases (1.9%) and hematoma formation in three cases (1.9%); one case reported ascent of the testis and another one had testicular atrophy in the follow-up period which extends now up to 3 years and we are still in follow-up with those cases. Conclusion: Our modified technique for extra Dartos pouch fixation seems to be a fast reliable method for orchiopexy; however, comparative studies and long-term assessment is still needed to establish this method.